The prison and the American imagination - Smith, Caleb (Yale studies in English, 2009)
How did a nation so famously associated with freedom become internationally identified with imprisonment? After the scandals of Abu Ghraib and Guantanamo Bay, and in the midst of a dramatically escalating prison population, the question is particularly urgent. In this timely, provocative study, Caleb Smith argues that the dehumanization inherent in captivity has always been at the heart of American civil society. Exploring legal, political, and literary texts - including the works of Dickinson, Melville, and Emerson - Smith shows how alienation and self-reliance, social death and spiritual rebirth, torture and penitence came together in the prison, a scene for the portrayal of both gothic nightmares and romantic dreams. Demonstrating how the "cellular soul" has endured since the antebellum age, The Prison and the American Imagination offers a passionate and haunting critique of the very idea of solitude in American life